2009
DOI: 10.1182/blood-2008-06-165340
|View full text |Cite
|
Sign up to set email alerts
|

Transferrin-a modulates hepcidin expression in zebrafish embryos

Abstract: The iron regulatory hormone hepcidin is transcriptionally up-regulated in response to iron loading, but the mechanisms by which iron levels are sensed are not well understood. Large-scale genetic screens in the zebrafish have resulted in the identification of hypochromic anemia mutants with a range of mutations affecting conserved pathways in iron metabolism and heme synthesis. We hypothesized that transferrin plays a critical role both in iron transport and in regulating hepcidin expression in zebrafish embry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 50 publications
2
51
0
Order By: Relevance
“…o-dianisidine staining was performed as described (Wingert, et al, 2004, 2005; Dooley, et al, 2008; Fraenkel, et al, 2009). At 38, 48, and 72 hpf, the number of heartbeats per minute were measured in wild-type embryos and sim1a morphants.…”
Section: Methodsmentioning
confidence: 99%
“…o-dianisidine staining was performed as described (Wingert, et al, 2004, 2005; Dooley, et al, 2008; Fraenkel, et al, 2009). At 38, 48, and 72 hpf, the number of heartbeats per minute were measured in wild-type embryos and sim1a morphants.…”
Section: Methodsmentioning
confidence: 99%
“…Transferrin is one of the negative acute phase proteins as well as being an iron carrier. Recently, it was reported that in zebrafish embryos transferrin plays a critical role in iron transport as well as regulating hepcidin expression [15]. Thereby a similar mechanism might modulate hepcidin expression in MHD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas our culture media contained bovine transferrin, it is extremely divergent from zebrafish Tf and is unlikely to cross-react with the zebrafish receptor. We therefore supplemented cultures with carp serum (carp Tf is 67% similar to zebrafish Tf, while human Tf is only 49% 38 ) or an Fe-SIH reagent that is able to diffuse across membranes and bypass the Tfr and DMT1 transporters normally required for mitochondrial iron import. 39 Addition of either reagent alone did not increase hemoglobinized erythroid cells compared with addition of zEpo ( Figure 6C).…”
Section: Purified Epo Increases In Vitro Erythroid Differentiationmentioning
confidence: 99%